Prepare the Way of the Lord - Hartvigsen, Kirsten Marie (De Gruyter, 2012)
This study analyzes an oral performance of the entire Gospel of Mark, with emphasis on involvement with characters and events, the emotional effects of such involvement, and how these processes maintain or shape the identity of those who hear the Gospel. Insights from cognitive poetics and psychonarratology illuminate the cognitive processes that take place during the performance. Consequently, previous research on the Gospel of Mark, which was conducted on the basis of narrative criticism, orality criticism, and performance criticism, is expanded with cognitive aspects.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Narrative Exegese; Sprechtheater; Erzähltheorie